Probing the interaction of solvents with the stationary phase of C18 high-performance liquid chromatographic column material by variable-temperature dependent 129Xe nuclear magnetic resonance spectroscopy - Chagolla, Danny; Mathias, Errol V.; Ba, Yong (Journal of Chromatography A, 2006)
VT 129Xe NMR was applied to probe the interactions of solvents having different polarity indices with the stationary phase of a RP-C18 HPLC column material. It was observed that the highly polar ethylene glycol molecules do not mix with the alkyl chains of the RP-C18 stationary phase and the solvent is unable to enter the pores and the spaces between the particles. Three phases in this sample are defined as stationary/xenon phase, xenon gas phase (in the pores and the spaces between the particles) and ethylene glycol/xenon phase. In contrast to ethylene glycol, the nonpolar solvent cyclohexane was observed to be well mixed with the RP-C18 stationary phase. The capillary rise effect allows the solvent to enter the pores and the spaces between the particles. Two phases in this sample are defined as stationary/cyclohexane/xenon phase and cyclohexane/xenon phases. The properties of ethyl acetate are between those of ethylene glycol and cyclohexane. The 129Xe NMR results show that the rational reversed phases should be conditioned from highly solvating to more polar solvents to remove the trapped air. The 129Xe NMR results also show that pure stationary phase exists only when a highly polar solvent is used in reversed-phase chromatography. For a solvent with lower polarity, a stationary/solvent phase actually forms. This, together with the mobile phase, determines the selective factor for separating mixtures.